2022
DOI: 10.36987/jes.v9i1.2520
|View full text |Cite
|
Sign up to set email alerts
|

Catatan Pembelajaran Jarak Jauh: Hasil Belajar Sains Dan Pembelajarannya Pada Mahasiswa Pendidikan Guru Sekolah Dasar

Abstract: Pembelajaran jarak jauh dan umumnya dilaksanakan secara daring yang sudah terlalu lama menimbulkan kekhawatiran terhadap hilangnya kemampuan belajar mahasiswa. Kekhawatiran tersebut perlu dibuktikan melalui monitoring terhadap proses dan hasil belajar. Tujuan dari penelitian ini mendeskripsikan hasil belajar sains dan pembelajarannya pada mahasiswa diera pandemi Covid-19. Penelitian dilakukan di Program Studi PGSD Universitas Mataram. Sampling dilakukan secara purposive. Sampel terdiri dari 192 mahasiswa yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…One of them is maximizing the function of pedagogy that combines social constructivism and critical theory in learning (Botes & Barnett, 2022). In the PGSD Study Program, the effectiveness of the RPS, especially in science learning, can be observed from student learning achievements in science courses (Syazali & Umar, 2022). In its implementation, learning was carried out during 16 face-to-face meetings, structured assignments, and independent study.…”
Section: Resultsmentioning
confidence: 99%
“…One of them is maximizing the function of pedagogy that combines social constructivism and critical theory in learning (Botes & Barnett, 2022). In the PGSD Study Program, the effectiveness of the RPS, especially in science learning, can be observed from student learning achievements in science courses (Syazali & Umar, 2022). In its implementation, learning was carried out during 16 face-to-face meetings, structured assignments, and independent study.…”
Section: Resultsmentioning
confidence: 99%
“…Students' science learning outcomes regarding the ability of products and SPS also show a positive trend. The category has reached good with a mastery of 70.97 [7]. This value itself has a grade of B+.…”
Section: Introductionmentioning
confidence: 95%
“…Hasil belajar sains ini lebih tinggi dibandingkan dengan hasil asesmen yang dilakukan pada tahun 2022. Secara rata-rata, nilainya berada pada angka 70.97, di mana grade-nya baik (Syazali & Umar, 2022). Hasil ini adalah evaluasi terhadap penerapan pembelajaran jarak jauh yang diterapkan pada saat pendemi Covid-19.…”
Section: Pembahasanunclassified